Representasi Perjuangan Mendapatkan Restu Keluarga oleh Tokoh Erwin dalam Film Cek Toko Sebelah 2 : Analisis Semiotika Charles Sanders Peirce - Andhika Anwar Pratama; Ade Budi Santoso (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Film as a form of mass media has an important role in the socio-cultural, artistic, political, as well as scientific realms. Cek Toko Lado 2 is a continuation of the story of the Chinese family of Koh Afuk which is in the comedy genre and directed by Ernest Prakasa. This film not only presents entertainment, but also presents family dynamics, parental expectations, and challenges in maintaining family business while building trust between fellow family members. The stories presented are able to illustrate the social reality of urban communities who are often faced with a dilemma between family interests and individual freedom. The purpose of this research is to analyze the struggle of Erwin's character in fighting for his love for Natalie and his efforts to get the blessing of his future in-laws. The research method used is qualitative with the approach of Charles Sanders Peirce's semiotic theory. The data source was obtained through direct observation of scenes and dialogues in the film, and reinforced by documentation and literature studies. The results of the study show that Erwin's struggle can be understood through three main elements in Peirce's semiotics, namely sign, object, and interpretant. First, the spirit of never giving up is reflected in Erwin's consistency in facing various obstacles. Second, the attitude of responsibility can be seen from Erwin's commitment to his career and the romantic relationship he is living. Third, the willingness to sacrifice is evident when Erwin prioritizes personal interests in order to gain the blessing of Natalie's family. In conclusion, this study emphasizes that films not only function as a means of entertainment, but also as a social learning medium that conveys moral messages about struggle, sacrifice, and the importance of trust in family relationships and romance. Thus, Cek Toko Lado 2 is able to be a relevant and inspiring social reflection for the audience, especially urban people who are facing the dynamics of family life and love.